Why do women prefer home births in Ethiopia? - Shiferaw Solomon; Spigt Mark; Godefrooij Merijn; Melkamu Yilma; Tekie Michael (BMC, 2013)
Abstract Background Skilled attendants during labor, delivery, and in the early postpartum period, can prevent up to 75% or more of maternal death. However, in many developing countries, very few mothers make at least one antenatal visit and even less receive delivery care from skilled professionals. The present study reports findings from a region where key challenges related to transportation and availability of obstetric services were addressed by an ongoing project, giving a unique opportunity to understand why women might continue to prefer home delivery even when facility based delivery is available at minimal cost. Methods The study took place in Ethiopia using a mixed study design employing a cross sectional household survey among 15-49 year old women combined with in-depth interviews and focus group discussions. Results Seventy one percent of mothers received antenatal care from a health professional (doctor, health officer, nurse, or midwife) for their most recent birth in the one year preceding the survey. Overall only 16% of deliveries were assisted by health professionals, while a significant majority (78%) was attended by traditional birth attendants. The most important reasons for not seeking institutional delivery were the belief that it is not necessary (42%) and not customary (36%), followed by high cost (22%) and distance or lack of transportation (8%). The group discussions and interviews identified several reasons for the preference of traditional birth attendants over health facilities. Traditional birth attendants were seen as culturally acceptable and competent health workers. Women reported poor quality of care and previous negative experiences with health facilities. In addition, women's low awareness on the advantages of skilled attendance at delivery, little role in making decisions (even when they want), and economic constraints during referral contribute to the low level of service utilization. Conclusions The study indicated the crucial role of proper health care provider-client communication and providing a more client centered and culturally sensitive care if utilization of existing health facilities is to be maximized. Implications of findings for maternal health programs and further research are discussed.